Short-Term Efficacy and Tolerability of Paroxetine Versus Placebo for Panic Disorder: A Meta-Analysis of Randomized Controlled Trials - Zhang, Beilin; Wang, Chao; Cui, Lexiang; Gao, Jiguo; Wang, Chenglin; Tan, Xiangyu; Fang, Shaokuan (Frontiers in Pharmacology, 2020)
Objective: To explore the short-term efficacy and tolerability of paroxetine in the treatment of panic disorder in adults. Methods: Multiple electronic databases were searched to find randomized controlled trials (RCTs) about paroxetine and panic disorder. The primary efficacy outcomes were the mean change from baseline in total number of full panic attacks and Clinical Global Impression-Severity of Illness (CGI-S) score, the proportion of participants with zero full panic attacks and with a 50% or greater reduction in the number of full panic attacks. The tolerability outcomes included withdrawal rate and the incidence of adverse events (AEs). Results: 13RCTs were included, the pooled analyses showed patients who received paroxetine experienced greater improvement in number of full panic attacks(total: MD=-1.96, 95%CI -3.45 to -0.47, P=0.010; ≥50% reduction: OR=1.66, 95%CI 1.08 to 2.55, P=0.02; zero full panic attacks: OR=1.70, 95%CI 1.42 to 2.03, P<0.00001) and CGI-S (MD=-0.37, 95%CI -0.74 to -0.01, P=0.05) than placebo. There was no evident difference in the total withdrawal rate (OR=0.91, 95%CI 0.76 to 1.08, P=0.26) and withdrawal rate due to AEs (OR=1.29, 95%CI 0.97 to 1.72, P=0.07) between two groups. Besides, withdrawal rate due to lack of efficacy or relapse (OR=0.44, 95%CI 0.31 to 0.63, P<0.00001) and the incidence of serious AEs (OR=0.42, 95%CI 0.23 to 0.79, P=0.007) in paroxetine group was lower than placebo group. Meanwhile, the incidence of any TEAEs (OR=1.32, 95%CI 1.05 to 1.64, P=0.02) in paroxetine group was higher in comparison with placebo. Conclusions: Paroxetine is an effective and well-tolerated short-term treatment for adults with panic disorder.